Implementasi Sistem Informasi Kearsipan Dinamis Terintegrasi (SRIKANDI) di Madrasah Aliyah Negeri Batam - Hisyam, Farhan; Mariyamah, Aam (ARCHIVIST: Indonesian Journal of Archival, 2025)
This research aims to determine the implementation of the Integrated Dynamic Archive Information System (SRIKANDI) in Madrasah Aliyah Negeri Batam. By identifying the successes and challenges faced in implementing this system, this research is expected to provide valuable insights for stakeholders to improve the efficiency and effectiveness of archive management in the madrasah environment. This study uses a qualitative type of research. The data obtained by the researcher is primary data collected through interviews with SRIKANDI user informants at Madrasah Aliyah Negeri Batam. The results of this study show that the use of the SRIKANDI application in Madrasah Aliyah Negeri Batam is optimal.